Comparative phosphoproteomics provides insights into the differences of porcine longissimus thoracis, semimembranosus, psoas major and semitendinosus muscles - Li Zhang; Wen Luo; Linlin Zhao; Longyun Li; Yizhong Huang (Food Chemistry: Molecular Sciences)
Different pork cuts vary in muscle fiber characteristics and meat quality, significantly affecting processing properties and consumer preference. However, the role of protein phosphorylation in meat quality variation in pork cuts remains unclear. Using a 4D label-free platform, we performed quantitative phosphoproteomic analysis on longissimus thoracis (LT), semimembranosus (SMM), psoas major muscle (PS) and semitendinosus (SMT), identifying 13,232 phosphopeptides from 3137 phosphoproteins, and over 1000 differentially accumulated phosphopeptides (DAPPs) in each of six comparison groups. Enrichment analysis showed that these phosphoproteins were enriched in sarcomere organization and muscle cytoskeleton pathways. A total of 184, 53, 75, and 691 unique DAPPs were identified in LT, SMM, PS, and SMT, respectively. Protein-protein interaction networks revealed that phosphoproteins regulated meat quality differences. Several key phosphoproteins, including ATP5F1A, ATP5F1C, FLNC, MDH2, BAG3, and AKT1, demonstrated significant associations with meat quality traits. These findings provide valuable insights for phosphoproteins that regulate meat quality in pigs.